2005
DOI: 10.1074/jbc.m410876200
|View full text |Cite
|
Sign up to set email alerts
|

Proteasome Inhibition Alters Glucose-stimulated (Pro)insulin Secretion and Turnover in Pancreatic β-Cells

Abstract: Metabolic labeling studies were conducted in freshly isolated mouse islets and a ␤-cell line (MIN6) to examine the effects of proteasome inhibition on glucose-stimulated (pro)insulin synthesis and secretion. Glucose-stimulated (pro)insulin synthesis, as determined by the incorporation of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
46
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(51 citation statements)
references
References 66 publications
5
46
0
Order By: Relevance
“…Hence, the present data indicate that proteasome inhibition in the ␤-cell did not prevent but stimulated the degradation of iNOS, thus suggesting more complex control mechanisms regulating the cellular balance of this protein. A similar paradoxical effect of proteasome inhibition in the ␤-cell was previously reported with regard to (pro)insulin, the degradation of which was increased in the presence of the proteasome inhibitor lactacystin (21). A paradoxical effect of proteasome inhibition has also been reported (20) in rat vascular smooth muscle.…”
Section: Discussionmentioning
confidence: 50%
“…Hence, the present data indicate that proteasome inhibition in the ␤-cell did not prevent but stimulated the degradation of iNOS, thus suggesting more complex control mechanisms regulating the cellular balance of this protein. A similar paradoxical effect of proteasome inhibition in the ␤-cell was previously reported with regard to (pro)insulin, the degradation of which was increased in the presence of the proteasome inhibitor lactacystin (21). A paradoxical effect of proteasome inhibition has also been reported (20) in rat vascular smooth muscle.…”
Section: Discussionmentioning
confidence: 50%
“…Kalbe et al (47) also observed an increase in insulin secretion from fetal islets exposed to lactacystin. However, another recent report (48) demonstrates that lactacystin decreases insulin release from islets exposed to high glucose without affecting the total insulin content. The same work shows that lactacystin decreases insulin synthesis and favors its degradation.…”
Section: Discussionmentioning
confidence: 99%
“…Despite this model's hypothetical nature, we suggest that it provides a useful platform for further investigation, On a more functional note, we suggest that regulation of UCP2 degradation by the ubiquitin-proteasome system serves to regulate it in line with other proteins. In the pancreatic b-cell, the proteasome is known to regulate proteins involved in the insulin secretion pathway such as ATP-sensitive potassium channels (Yan et al, 2005), voltage-dependent calcium channels (Kawaguchi et al, 2006) and proinsulin levels (Kitiphongspattana et al, 2005). In all these cases, proteasome inhibition leads to decreased glucose-stimulated insulin secretion, suggesting that proteasome dysfunction may be one of the molecular mechanisms of the b-cell impairment seen in type 2 diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%